Incorporación de las masculinidades en el marco de la Agenda Climática global: Análisis y perspectivas (2024)
The report aims to identify the conceptualization of masculinities within the framework of the international climate agenda. It utilizes hermeneutics as a method of qualitative research to comprehend the approach to these themes in international arenas and their evolution in recognizing the differentiated impacts of climate change.